2022
DOI: 10.3390/cells11071164
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 at the Host-Tumor Interface: STAT3 in Biomolecular Condensates in Cancer Cells

Abstract: It was recognized over 30 years ago that the polyfunctional cytokine interleukin-6 (IL-6) was an almost invariant presence at the host-tumor interface. The IL-6 in the tumor microenvironment was produced either by the cancer cell or by host stromal cells, or by tumor-infiltrating immune cells, or all of them. IL-6 effects in this context included local changes in tumor cell-cell and cell-substrate adhesion, enhanced motility, epithelial to mesenchymal transformation (EMT), and changes in cell proliferation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…One common mediator of IL-6 signaling is the signal transducer and activator of transcription 3 (STAT3) [ 25 , 26 ]. In our experiments, STAT3 phosphorylation was observed as early as 15 min after stimulation with IL-6, and persisted for up to 24 h ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…One common mediator of IL-6 signaling is the signal transducer and activator of transcription 3 (STAT3) [ 25 , 26 ]. In our experiments, STAT3 phosphorylation was observed as early as 15 min after stimulation with IL-6, and persisted for up to 24 h ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the 7β-estradiol-bound estrogen receptor inhibits IKK activity and causes IκB protein degradation, blocking DNA binding by NF-κB. Consequently, this leads to a reduction in the intensity of the inflammatory response during the course of various diseases, including cancer [ 47 , 48 , 49 ]. Moreover, we also observed a significant increase in the expression of IL-6 in the case of the T1 stage compared to the Ta stage.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 IL-6 is a unique pleiotropic cytokine, with proinflammatory and stimulatory activity on a wide variety of cell types, whose expression can be increased in cancer cells via p53 mutations, with resultant increased STAT3 transcriptional signaling. 34 IL-6 can be upregulated by tissue damage and/or be a secondary response to proinflammatory cytokines such as TNF-α, and is thought to contribute to chronic inflammatory activation via the production of C-reactive protein. 35 Research has also suggested that only very low circulating levels of IL-6 are needed to affect inflammatory cascades, 36 which may be one reason this immune marker had the strongest association in our study.…”
Section: Discussionmentioning
confidence: 99%